DETERMINAN PENGGUNAAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) DI WILAYAH KERJA PUSKESMAS SAIL KECAMATAN SAIL PEKANBARU - Mona Dewi Utari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
IUD is contaceptive that is effective enough to prevent pregnancy, but the number of family planning IUD acceptors is still low compared with other contraceptives even has the advantage that a low failure rate of around 1% a long service life. Independent variables of knowledge of IUD, education, occupation, age, parity, income, husband support, information, and disease history. This research is a quantitative approach by case control study. The technique sampling is systematic random sampling and the instrument is a questionnaire. The result were obtained from 390 respondents 50% were using IUD and 50% does not use an IUD. Conclusion of 9 variables were influence to the use of IUD there are 4 influence to the use contraceptives IUD, that is parity, disease history, provision of information and knowledge. In this study, parity is dominant factor (OR= 0,657). Suggestion: the communication of information and education and support health workers can support successful long – term contraceptive methods.